Corrective Justice and Its Significance on the Private Law (Journal of Indonesian Legal Studies, 2022)
This article attempts to explore corrective justice and its significant role in private law. There are many justice perspective on private law, but corrective justice is part of the view that have significant role in the work of private law. Breaking the private property right charges someone to take responsibility. To what extent private law rules responsibility of the someone. Corrective justice can be meassurement to take responsibility. Corrective justice can be traced back to Aristotle's ideas of justice and Kant's ideas of rights. Hans Kelsen sharply criticized the concept of corrective justice for only proposing formal ideas without touching anything substantial. Apart from this criticism, corrective justice remains very important in private law studies because it provides solutions between two private actors in which one benefits from the losses experienced by the other. So far, the dispute settlement mechanism in private law gives the winning party a full share, while the loser does not receive any share at all. Corrective justice offers a quantitative measure that balances what the defendant is deducting and what is added to the claimant's loss. The application of this principle encourages the creation of equal punishment between the disputed parties.